2022
DOI: 10.1186/s43591-022-00026-2
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in the Mediterranean marine environment: a combined bibliometric and systematic analysis to identify current trends and challenges

Abstract: In recent decades, the potential toxicological and environmental effects of microplastics (MPs) in the Mediterranean Sea region have received growing attention. The number of studies in this area has increased; however, presently there is no scientometric perspective addressing this topic. The purpose of this study was to identify the intellectual base and research front using the visualization and analysis software, CiteSpace, in combination with a systematic review. We retrieved 150 articles, published in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 149 publications
(144 reference statements)
0
8
0
Order By: Relevance
“…Can-Güven ( 2020 ) studied microplastics as emerging pollutants in the atmospheres. Similarly, Papadimitriu and Allinson ( 2022 ) reported on MPs in the marine environments of the Mediterranean Sea. Also, Palmas et al ( 2021 ) reported about MPs in wastewater treatment plants, while Zhou et al ( 2022 ) investigated MPs and/or nanoplastics in the sea, ocean, beach, bay, gulf, estuary, coastline, or shoreline environments.…”
Section: Introductionmentioning
confidence: 74%
“…Can-Güven ( 2020 ) studied microplastics as emerging pollutants in the atmospheres. Similarly, Papadimitriu and Allinson ( 2022 ) reported on MPs in the marine environments of the Mediterranean Sea. Also, Palmas et al ( 2021 ) reported about MPs in wastewater treatment plants, while Zhou et al ( 2022 ) investigated MPs and/or nanoplastics in the sea, ocean, beach, bay, gulf, estuary, coastline, or shoreline environments.…”
Section: Introductionmentioning
confidence: 74%
“…İskenderun Bay is located inside the biggest plastic hotspot of the Mediterranean Sea (Papadimitriu & Allinson, 2022). As result of urbanized coastal line and intense industrial activities, severe microplastic pollution has been reported in the study area (Güven et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Fibers released during the production of textiles and clothing made of synthetic materials [28] Toys, rubber, kitchen utensils, electrical wires, and interior paint [29] Polyethylene (PE), polypropylene (PP), and polystyrene (PS) particles in cosmetic and medical products [30] Textile fbers originating from clothing due to daily use or washing processes and released from textile manufacturing plants [31] Cosmetic formulations often contain industrially produced microspheres and plastic particles [28] It arises during the consumption and design of plastic products (for example, when plastic bottles degrade) or when macroplastics decompose into MPs [32] Product of the industrial shot-blasting process using microplastics as an abrasive agent [31] Te marketing and use of disposable plastics, focus on straws and plastic bags [33] Synthetic grass (turf ) on the football pitch [34] Material obtained from fshing nets [35] Release of drilling fuids from oil and gas exploration activities, as well as in industrial abrasive processes [34] LDP (low-density polyethylene) sheeting is commonly used in agriculture to maintain soil moisture, control weeds, and regulate temperature, a process known as plastic sheeting [34] and supraglacial [43] wastes and eventually becoming widely distributed causing damage to biotic systems by entering the food chain through direct or indirect consumption, and indirect consumption occurs when food is consumed which transports the MP particles to places further away from their point of origin [44].…”
Section: Secondary Mpsmentioning
confidence: 99%